O resgate do gótico e do sobrenatural na literatura brasileira : uma leitura de “Bento”, de André Vianco - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
In this dissertation, my central objective is to promote the rescue and valorization of gothic and supernatural literature in the context of Brazilian literature, with a specific focus on "Bento" (2003) by André Vianco. Utilizing a methodological approach based on bibliographic research, this investigation is grounded in theoretical contributions from renowned scholars such as Freud (1976), Kristeva (1982), Burke (1993), Bosi (2006), Candido (2009), Botting (1996, 2008), Punter (1996), Simon (1991), Lecoutex (2005), Melton (2008), França (2013, 2016, 2017, 2018, 2019), Vasconcelos (2002), Mello (2005), Nestarez (2022), Freitas (2018), S. Santos (2002), and M. Santos (2010) to support the conducted analysis. The work begins with an exploration of the origins and evolution of the gothic genre in global literature, contextualizing its relationship with cultural and social dynamics. Next, a panorama of Brazilian gothic and supernatural literature is outlined, emphasizing the identification of its distinctive characteristics and the importance of preserving this unique literary tradition. The central focus then shifts to the work of André Vianco, especially "Bento" (2003), with an analysis that encompasses aesthetic theories of the abject, strange, and sublime. The relevance of cultural taboos in gothic and supernatural literature is also explored, adopting a psychoanalytic perspective based on Freud's taboo theory, as well as highlighting the aesthetic choices made by authors to address taboo issues and their implications in society. The dissertation also underscores gothic literature as a form of cultural resistance, challenging predominant cultural norms in Brazil and offering a relevant counterpoint in the literary scene. Thus, with this study, I provide an analysis of the presence and influence of gothic and supernatural literature in Brazilian literature, emphasizing the existence of a Brazilian gothic tradition and the urgent need to value and rescue this rich literary production in our country.
The rescue of the gothic and the supernatural in brazilian literature : a reading of “Bento”, by André Vianco
Keywords: Bento; Literatura gótica; Teorias estéticas; Apagamento gótico brasileiro; Resistência cultural; Gothic literature; Aesthetic theories; Brazilian gothic erasure; Cultural resistance; LETRAS::LITERATURA BRASILEIRA